2022
DOI: 10.3892/etm.2022.11441
|View full text |Cite
|
Sign up to set email alerts
|

Verbascoside potentiates the effect of tyrosine kinase inhibitors on the induction of apoptosis and oxidative stress via the Abl-mediated MAPK signalling pathway in chronic myeloid leukaemia

Abstract: Verbascoside (Verb) may exhibit potential antitumour activities in leukaemia. The present study investigated the effect of Verb, in combination with imatinib (IM), dasatinib (Das), lipopolysaccharide (LPS) and TNF, on cell survival, Abl expression, apoptosis, oxidative stress and the MAPK pathway in chronic myeloid leukaemia (CML) cells. Cell viability was determined using the WST-8 assay in K562 and R-K562 cells treated with Verb and/or IM, Das, LPS and TNF. Apoptosis and DNA damage in CML cells was detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…We first investigated the effects of imatinib on proliferation, survival, and DDX5 expression in K562 cells. With reference to previous reports [60,61], we chose two concentrations (1 and 2 µM) of imatinib to test their effects. However, there was no significant difference in the suppressive effects of 1 µM and 2 µM imatinib on them (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…We first investigated the effects of imatinib on proliferation, survival, and DDX5 expression in K562 cells. With reference to previous reports [60,61], we chose two concentrations (1 and 2 µM) of imatinib to test their effects. However, there was no significant difference in the suppressive effects of 1 µM and 2 µM imatinib on them (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the drug-induced oxidative stress exaggeration in leukemic cells could intensify the genotoxic effects of conventional therapy, facilitating the activation of programmed cell death ( Yang et al, 2018 ). In fact, recent findings showed that the stimulation of oxidative stress in CML, using compounds such as tyrosol derivatives, verbascoside, and zerumbone, promotes mitochondrial membrane potential dissipation, caspase activation, and apoptosis ( Rajan et al, 2015 ; Abdelkafi-Koubaa et al, 2022 ; Akgun-Cagliyan et al, 2022 ). Therefore, the strategy of deliberately increasing ROS to cytotoxic levels for leukemia cells seems to be very appealing, and our data are in agreement.…”
Section: Discussionmentioning
confidence: 99%
“…Plant-derived verbascoside can block CD44 dimerisation [51], and it was shown to induce apoptosis in a model of CML, possibly by mediating p38-MAPK/JNK and Caspase-3 signalling, although the role of CD44 was not explored here [52]. CD44 is highly expressed within normal, CML and AML CD34 + CD38 + and CD34 + CD38 − BM cells [53•], likely making it unsuitable as a CML LSC biomarker and a cancer-specific therapeutic target, but downstream signalling may be targetable.…”
Section: Adhesion Mechanismsmentioning
confidence: 99%